2015
DOI: 10.1002/asi.23564
|View full text |Cite
|
Sign up to set email alerts
|

Data sharing for the advancement of science: Overcoming barriers for citizen scientists

Abstract: Systematic study of data sharing by citizen scientists will make a significant contribution to science because of the growing importance of aggregated data in dataintensive science. This article expands on the data sharing component of a paper presented at the 2013 ASIST conference. A three-phase project is reported. Conducted between 2011 and 2013 within an environmental voluntary group, the Australian Plants Society Victoria (APSV), the interviews of the first phase are the major data source. Because the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 41 publications
(77 reference statements)
3
9
0
Order By: Relevance
“…In other words, the location was considered low risk, hence, interacting with the other was deemed safe. This finding supports the argument that people tend to share information with one another at places they consider safe or low risk (Ibrahim and Allen, 2012;Williamson et al, 2016;Wilson, 2010). The finding also shows that place is not only a container of information sharing (Savolainen, 2009) but also an embodiment of the values and beliefs of the people.…”
Section: Discussionsupporting
confidence: 84%
“…In other words, the location was considered low risk, hence, interacting with the other was deemed safe. This finding supports the argument that people tend to share information with one another at places they consider safe or low risk (Ibrahim and Allen, 2012;Williamson et al, 2016;Wilson, 2010). The finding also shows that place is not only a container of information sharing (Savolainen, 2009) but also an embodiment of the values and beliefs of the people.…”
Section: Discussionsupporting
confidence: 84%
“…On reading the literature, we also come to the view that there are still some barriers concerning the attitudes (i.e., hesitancy) of scientists when confronted with the use and collection of data by non-experts [3]. This supports previous experiments addressing aspects like data handling and preservation, responsibility (e.g., intellectual property), trust (perceptions of data quality), and lack of a shared disciplinary background [60]. Another set of contributions regards the study of complex work in crowd science [26].…”
Section: Open Issues In Crowd-ai Sciencesupporting
confidence: 75%
“…Several studies have highlighted the importance of data sharing (Dallmeier-Tiessen et al, 2014;Williamson, Kennan, Johanson, & Weckert, 2016). Data sharing refers to "the voluntary provision of information from one individual or institution to another for purposes of legitimate scientific research" (Boruch, 1985, p. 89).…”
Section: Data Sharingmentioning
confidence: 99%
“…Previous research on data sharing has included studies on barriers and enablers of data sharing (Dallmeier-Tiessen et al, 2014;Tenopir et al, 2011;Williamson et al, 2016). For instance, Tenopir et al (2011) found that barriers to effective data sharing are rooted in the practice and culture of the research process as well as the researchers themselves.…”
Section: Data Sharingmentioning
confidence: 99%